Interacciones con sentido: efectos positivos de la tertulia literaria - Barrientos Mollo, Roberto (2017)
An important duty of educators and policy makers is to close that gap between what is known and what is done. This text seeks to be a contribution of this task. Literary dialogic discussions are proposed as an effective strategy to ensure participation and interaction between students for better learning